Using the Methodology for the Comprehensive Assessment of Scientific and Technological Projects to Estimate Risks of their Failure - A. V. Komarov; K. A. Komarov; K. V. Shurtakov (Ekonomika Nauki, 2021)
The article proposes approaches to assessing the risk of non-implementation of scientific and technological projects, based on the analysis of data from institutions for innovative development of information, and carried out following the requirements of a comprehensive assessment of projects’ technological readiness. One of the approaches presented allows you to build a matrix for subsequent analysis that describes the possibility of a project oving to a higher level of development, and the second is based on identifying empirical dependencies between the level of readiness of the project being executed and the risk of violating its deadlines. Examples of applying  the developed approaches for practical tasks on program activities of target programs in the field of research and development in priority areas of the scientific and technological complex of Russia are given. The described models are intended for use in the governing bodies of innovative development institutions to increase the implemented support programs’ efficiency.